A quality of life assessment tool for haemodialysis patients in Abu Dhabi. (2nd May 2019) - Jamilano, Katheryn; Fowler, John; Richards, Marie; Cooper, Christine Whitney; Richards, Nick
Abstract : When assessing the quality of life of patients undergoing haemodialysis, it is important to use a reliable assessment tool. This article discusses the results of a small-scale survey designed to elicit the quality of life of patients undergoing haemodialysis, highlighting how assessment tools can be utilised to improve quality of care